A radius of trust? Contrasting insights from experiments and survey data - Martin C. Parlasca; Daniel Hermann; Oliver Mußhoff (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
A person's reach of efficient economic activities is strongly influenced by the extent to which she grants trust towards other people. The radius of trust has recently gained interest as a concept to elucidate the underlying principles of how far a person extends her trust. However, empirical research on the radius of trust has up to now only been grounded in survey data. In this paper we use an incentivized experiment, namely the trust game, and two sets of survey questions to i) identify and localize the radius of trust and ii) contrast experimental and survey results regarding the radius of trust. To do so, we measure trust layers of 394 semi-nomadic pastoralists in rural Kenya conditional on three levels of social distance: trust towards people from one's own village, trust towards people from a neighboring village, and trust towards city dwellers from the county capital. Experimental data suggest that city dwellers are excluded from the radius of trust and face particularly low trust levels, while people from one's own village and from neighboring villages are inside the radius of trust. Survey data do not suggest any clear-cut radius of trust. Implications for development practitioners and further research on the radius of trust are discussed.
Keywords: C93; D01; O12; 330; radius of trust; social distance; trust; field experiment; pastoralism; Kenya